Development of Portable Solar-Tracked PV Powerbank Station - Yusoff, Muhamad Farhan; Sy Yi, Sim (Evolution in Electrical and Electronic Engineering, 2023)
When it satisfies the most recent societal standards for operating silently and without pollution, the use of solar panels is growing in popularity. Solar trackers have been developed to improve the energy produced by solar panels even further. It was developed to improve the effectiveness of solar panels, hence capturing more voltage. The microcontroller for this project moves the solar panel so it always faces the sun using an Arduino processor. The LDR detector, which is used to determine the direction of the sun’s rays before providing the signal to the Arduino processor, is what causes this solar panel to move. Despite the comparatively high expense of employing solar trackers, it is crucial to utilize all of the sun’s limitless and pollution-free energy by making solar panels more efficient. It is intended that if solar trackers are used more frequently, the price will drop, and more people would be able to afford them. The servo motor’s rotational speed will be shown on the LCD screen display. Based on the programming that has been done on the Arduino ide programming, the Arduino Mega microprocessor powers this project. This project’s goals have been attained as a consequence of the tests that have been run. It is envisaged that numerous parties will utilize this solar radiation tracker in the future. This final year project introduces the project that stores solar energy from the sun and transforms it into electricity with the help of Sensors. This project employs an LDR that detects changes in light intensity and adjusts the output, accordingly, causing the solar panel to change direction to follow the light path. This project consists of several types of equipment such as USB charging, socket, LDR sensors, and servo motor. Arduino software to produce command/coding, allowing it to be called a Portable Solar-Tracked PV Powerbank Station.